O uso de técnicas geoestatísticas para o mapeamento da vulnerabilidade natural do Aquífero Guarani em área de recarga: aplicação na região de Ribeirão Bonito - SP - Ferreira, Gabriela Trigo [UNESP] (2014)
The Guarani Aquifer has recharge areas where it is exposed and therefore subject to contamination by effluents and tailings deposited on soils that cover this areas. Therefore it is extremely important the knowledge of his natural vulnerability, contributing for their protection at all levels. The project presents an alternative and quantitative form of mapping the natural aquifer vulnerability by applying the method AVI. The AVI Index, used as a measure of vulnerability, requires the ratio between the thickness of the unsaturated zone and the permeability of the tested point. Given that the AVI Index, target of this study, presented in classes of vulnerability, it was opted for the use of non-parametric geostatistics, ie, calculating the average values for the thickness of the unsaturated zone and for the permeability . It was used the indicative kriging to obtain the results since it can provide the results in probabilistic classes. The result is represented by the maps of the permeability and the vulnerability of the study area located in Ribeirão Bonito-SP